2023
DOI: 10.1039/d3dt01478a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and electrocatalytic properties of PbTiO3: unveiling the effect of strain and oxygen vacancy

L. Bendaoudi,
T. Ouahrani,
A. Daouli
et al.

Abstract: First-principles calculations based on density-functional theory have been used to investigate the effect of biaxial strain and oxygen vacancy on the electronic, photocatalytic, and electrocatalytic properties of PbTiO3 oxide. Our...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…The optical modes are displayed in Table 1 together with those of bulk-PbTiO 3 . 18 We can note that the wavenumbers of the phonons for the 2D structure are higher than those obtained for the 3D structure. We provide the eigenvector associated with each atomic displacement in Fig.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The optical modes are displayed in Table 1 together with those of bulk-PbTiO 3 . 18 We can note that the wavenumbers of the phonons for the 2D structure are higher than those obtained for the 3D structure. We provide the eigenvector associated with each atomic displacement in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…16 Due to the fact that the toxicity of this material could be avoided by adding transparent phosphate salt, 17 this material is becoming a matter of increased interest. 18 Global minimum calculations for the free-energy surface through the crystal structure analysis by the particle swarm optimization methodology 19 showed that the isolation of PbTiO 3 in a 2D monolayer gives a stable structure. The question that arises is whether the 2D structure of PbTiO 3 has the unique properties shown by the other HER 2D ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation